Detection of short‐term slow slip events along the Nankai Trough, southwest Japan, using GNSS data. Issue 6 (13th June 2013) - Nishimura, Takuya; Matsuzawa, Takanori; Obara, Kazushige
Abstract: [1] We detected short‐term slow slip events (SSEs) previously observable only with tilt and strain data along the Nankai Trough, southwest Japan, using GNSS (Global Navigation Satellite System) data. Offsets detected in GNSS time series using Akaike's information criterion helped automatically identify 207 episodes with a motion direction opposite to that of the relative plate motion from June 1996 to January 2012. By nonlinear inversion of the detected displacement, we estimated rectangular fault models for 133 probable and 25 possible short‐term SSEs over 15 years. The SSE moment magnitudes range from 5.5 to 6.3. Most SSE fault models are located in a narrow band of non‐volcanic tremors on the interfaces of the subducting Philippine Sea Plate. Large SSEs (moment magnitude, M w, ≥6) often occur in western and central Shikoku. The cumulative slip is distributed heterogeneously along the strike, generally decreasing eastward with the maximum slip (~50 cm) in western Shikoku. No definite short‐term SSEs were found in the Kii Channel, but several short‐term SSEs occurred in Ise Bay. Both regions are known as tremor gaps. The local maximum of the cumulative slip fills in the tremor gap located in Ise Bay. The long‐term rate of short‐term SSE cumulative moment increased by threefold around 2003 in eastern Shikoku, whereas it was almost constant in other regions. Comparison with short‐term SSE catalogues using tilt data suggests that both this study and previous studies missed some SSEs along the Nankai Trough. A combination of geodetic data is important in the monitoring of the spatiotemporal distribution of short‐term SSEs. Key Points: Short‐term slow slip events along the Nankai Trough are detected using GNSS data Non‐uniformly distributed SSEs (>150) occurred along the strike over 15 years The ETS zone had a gap in cumulative SSE slip in Kii Channel, but not in Ise Bay